MENINGKATKAN KESEHATAN MASYARAKAT BERSAMA IBU-IBU PKK DAN LANSIA DI DESA TATAH LAYAP - Novia Ariani; Sevy Hartati; Taufik Karami; Zahratunnisa (Jurnal Bakti untuk Negeri, 2023)
Community Service activities carried out in Tatah Layap Village are one of the efforts to improve community health with PKK mothers and the elderly (elderly). Tatah Layap Village is a village that has potential in the agricultural sector. The level of knowledge of PKK women and the elderly about the benefits of light exercise and the utilization of natural materials that can be used as an alternative treatment is still very limited. This activity aims to improve the health of the people in Tatah Layap Village regarding the benefits of gymnastics, red spinach cultivation, making red spinach projects and the use of the leaves of balikai (Stenochlaena palustris) as blood-boosting tea (Anemia). This activity was carried out using a method which consisted of several stages, namely field observation, planning, socialization, red spinach cultivation practices and the use of the leaves ofelakai (Stenochlaena palustris) as a blood-boosting tea (Anemia) and evaluation. The activity participants were PKK mothers and the elderly (seniors) in Tatah Layap Village with the target number for each activity being 25 respondents. The conclusion from the activities carried out was that the community received education about the benefits of gymnastics, cultivating red spinach, making red spinach projects and using the leaves ofelakai (Stenochlaena palustris) as a blood-boosting tea (anemia). In addition, the community can use the yard of the house as a small-scale garden and the community can make hydroponics a business field which is expected to improve the family economy.